Alteration of methylation status in archival DNA samples: A qualitative assessment by methylation specific polymerase chain reaction. (9th August 2020) - Iyer, Gayatri Rangarajan; Hasan, Qurratulain
Abstract: DNA methylation is an epigenetic mechanism that regulates gene expression, which also facilitates genomic imprinting. Genomic imprinting is responsible for differential expression of genes based on parent of origin. Altered methylation of parental alleles results in imprinting disorders diagnosed by methylation specific polymerase chain reaction (MS‐PCR) technique. With increasing evidence of genes under epigenetic influence, methylation studies are extensively performed on archival samples. To evaluate effect of storage and storage conditions on DNA methylation, a systematic MS‐PCR based analysis was planned on an imprinted gene, SNRPN, located on chromosome 15q11.2. It was assessed by MS‐PCR on fresh, 4 −20, and −80°C stored DNA samples for different time periods for systematic evaluation of methylation status. Technical factors like type of sample processing, method of DNA isolation, primer region polymorphism, sample heterogeneity were also evaluated. DNA methylation was observed to be altered for SNRPN gene after storage at −80°C from 2 months onwards. Long‐term storage of DNA at −80°C results in altered DNA methylation status. This may lead to false MS‐PCR diagnosis of imprinting disorders. Our proof of concept study should be followed with quantitative validation since the findings have critical implications in the present era of biobanking.